2019
DOI: 10.1111/cei.13372
|View full text |Cite
|
Sign up to set email alerts
|

Kidney injury enhances renal G-CSF expression and modulates granulopoiesis and human neutrophil CD177 in vivo

Abstract: Summary Kidney injury significantly increases overall mortality. Neutrophilic granulocytes (neutrophils) are the most abundant human blood leukocytes. They are characterized by a high turnover rate, chiefly controlled by granulocyte colony stimulating factor (G‐CSF). The role of kidney injury and uremia in regulation of granulopoiesis has not been reported. Kidney transplantation, which inherently causes ischemia–reperfusion injury of the graft, elevated human neutrophil expression of the surface glycoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Particularly CD274 (PD-1L) was enriched in cluster 1 compared to cluster 2, supporting the potential of neutrophils to progress toward a suppressive phenotype in severe COVID-19 ( Figure S6 J). Interestingly, CD177 is expressed in pre-neutrophils and persisting in cluster 1 further highlighting the newly emerging character of this cluster ( Volkmann et al., 2020 ).…”
Section: Resultsmentioning
confidence: 92%
“…Particularly CD274 (PD-1L) was enriched in cluster 1 compared to cluster 2, supporting the potential of neutrophils to progress toward a suppressive phenotype in severe COVID-19 ( Figure S6 J). Interestingly, CD177 is expressed in pre-neutrophils and persisting in cluster 1 further highlighting the newly emerging character of this cluster ( Volkmann et al., 2020 ).…”
Section: Resultsmentioning
confidence: 92%
“…S6G ). However, expression of CD177, CD274 (PD-L1) and zinc finger DHHC domain-containing palmitoyl transferases ZDHHC19, indicative of an immature and suppressive granulocyte phenotype (Volkmann et al, 2020), was specifically observed in patients with severe COVID-19 ( Fig. 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…4). In IRI or unilateral ureteral obstruction (UUO) mice, G-CSF is upregulated and the number of neutrophils increases in the injured kidney 30 . IL-12 and IL-33 work together as a stimulant to invariant natural killer T cells in the kidney and promote neutrophils and monocytes/macrophage infiltration into the organ 31 .…”
Section: Discussionmentioning
confidence: 99%